Understanding Generation Z’s adaptive performance: the role of core self-evaluation and harmonious work passion - Koespono, Dwiarko Nugrohoseno; Fendy Suhariadi; Praptini Yulianti; Reynaldi Dwi Junianta (Universitas Negeri Surabaya, Indonesia, 2024)
The COVID-19 pandemic has forced a lot of sectors in society to adapt to the new era. This also impacts the industrial world, especially Generation Z entering the job market. Generation Z is required high adaptive performance to help them adapt, collaborate, and develop management and self-motivation skills. This research aims to analyse the influence of core self-evaluation and harmonious work passion on the adaptive performance of Generation Z after the COVID-19 pandemic. The research used a quantitative approach and purposive sampling techniques to obtain 49 respondents. The results show an influence of core self-evaluation on harmonious work passion and an influence of harmonious work passion on adaptive performance. However, the results show no influence of core self-evaluation on adaptive performance. The overall dynamics emphasise that core self-evaluation as a psychological foundation and harmonious work passion as a positive work experience collectively create an environment where Generation Z not only navigate change effectively but also actively contribute to innovation and organisational growth.